PROSPECTIVE STUDY ON THE EFFECTIVENESS OF PLATELET-RICH PLASMA IN MANAGING CHRONIC PLANTAR FASCIITIS - BASHA, A. M. ILIAS; RASOOL, SHAIK; ANUSHA, K. (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objectives of this study were as follows: (1) Assess the impact of a single dose of platelet-rich plasma (PRP) injection on visual analog scale (VAS) scores for heel pain. (2) Evaluate the functional outcome scores following PRP treatment for chronic plantar fasciitis. (3) Measure and confirm the restoration of plantar fascia thickness through ultrasound (USG) assessments. (4) Determine the safety and viability of local PRP injection as a treatment option for individuals with chronic plantar fasciitis. Methods: This hospital-based prospective case series, spanning January 2019 to January 2020, enrolled 40 participants aged 25–65 with unilateral, persistent plantar fasciitis resistant to conservative treatment. Exclusion criteria included BMI ≥30, various pathologies, and recent injections. Ethical clearance was obtained, and participants received autologous PRP injections, with ultrasound measuring plantar fascia thickness. Post-injection, patients were monitored for adverse reactions, initiated stretching exercises, and progressed to weight-bearing activities after 6 weeks. Results: The study cohort, averaging 45 years (standard deviation [SD] 7.7), primarily comprised females with the right-foot prevalence. Symptom duration averaged 20 weeks (SD 4.5). Pre-injection VAS scores (6.7±1.2) significantly improved at 6 weeks (2.9±0.6) and 12 weeks (2.0±0.9) post-PRP injection (p<0.001). Plantar fascia thickness reduced from 5.1 mm (SD 0.6) to 4.1 mm (SD 0.5) at 12 weeks (p<0.001) and regular foot thickness: 3.7 mm (SD 0.5). Conclusion: The study reveals that a singular PRP injection brings about substantial and clinically meaningful enhancements in heel pain, functional outcomes, and the restoration of plantar fascia thickness, supported by ultrasound measurements. This underscores local PRP injection as a viable and safe therapeutic choice for those grappling with chronic plantar fasciitis.